Bobolink (Dolichonyx oryzivorus) Declines Follow Bison (Bison bison) Reintroduction on Private Conservation Grasslands - Kaplan, Rachel H.; Rosamond, Kristen M.; Goded, Sandra; Soultan, Alaaeldin; Glass, Alex; Kim, Daniel H.; Arcilla, Nico (Animals (Basel), 2021)
Among the most rapidly declining birds in continental North America, grassland birds evolved with American bison (Bison bison) until bison nearly became extinct due to overhunting. Bison populations have subsequently rebounded due to reintroductions on conservation lands, but the impacts of bison on grassland nesting birds remain largely unknown. We investigated how bison reintroduction, together with other land management and climate factors, affected breeding populations of a grassland bird species of conservation concern, the Bobolink (Dolichonyx oryzivorus). We quantified population changes in Bobolinks over an 18-year period in conservation grasslands where bison were reintroduced, compared with adjacent grasslands grazed by cattle and where hay was harvested after the bird breeding season. Four years after bison reintroduction, the bison population in the study area had doubled, while Bobolink abundance declined 62% and productivity declined 84%. Our findings suggest that bison reintroduction as a conservation strategy may be counterproductive in grassland fragments where overgrazing, trampling, and other negative impacts drive declines in grassland breeding birds. Where bird conservation is an objective, small grassland reserves may therefore be inappropriate sites for bison reintroduction. To maximize conservation benefits to birds, land managers should prioritize protecting grassland birds from disturbance during the bird breeding season.